Determining Diversity of Freshwater Fungi on Decaying Leaves: Comparison of Traditional and Molecular Approaches - Nikolcheva, Liliya G. (American Society for Microbiology, 2003)
Traditional microscope-based estimates of species richness of aquatic hyphomycetes depend upon the ability of the species in the community to sporulate. Molecular techniques which detect DNA from all stages of the life cycle could potentially circumvent the problems associated with traditional methods. Leaf disks from red maple, alder, linden, beech, and oak as well as birch wood sticks were submerged in a stream in southeastern Canada for 7, 14, and 28 days. Fungal biomass, estimated by the amount of ergosterol present, increased with time on all substrates. Alder, linden, and maple leaves were colonized earlier and accumulated the highest fungal biomass. Counts and identifications of released conidia suggested that fungal species richness increased, while community evenness decreased, with time (up to 11 species on day 28). Conidia of Articulospora tetracladia dominated. Modifications of two molecular methods—denaturing gradient gel electrophoresis (DGGE) and terminal restriction fragment length polymorphism (T-RFLP) analysis—suggested that both species richness and community evenness decreased with time. The dominant ribotype matched that of A. tetracladia. Species richness estimates based on DGGE were consistently higher than those based on T-RFLP analysis and exceeded those based on spore identification on days 7 and 14. Since traditional and molecular techniques assess different aspects of the fungal organism, both are essential for a balanced view of fungal succession on leaves decaying in streams.